Liberalism is not enough : race and poverty in postwar political thought - Averbeck, Robin Marie (University of North Carolina Press, 2018)
"In this intellectual history of the fraught relationship between race and poverty in the 1960s, Liberalism is not enough offers a sustained critique of the fundamental assumptions that structured thought and action on the postwar American left. Focusing on the figures associated with 'Great Society liberalism' like Daniel Patrick Moynihan, David Riesman, and Arthur Schlesinger Jr., Robin Marie Averbeck argues that these thinkers helped construct policies that never truly attempted a serious attack on the sources of racial inequality and injustice"--